A Research on Adult Learners’ Performance in English Language in Literacy Centres in Imenti-North Sub-County, Meru County Kenya - Muriungi, Carolyne Mwendwa (Journal of Education and Practice, 2023)
Purpose: This paper investigated the learning of English as a second language in adult post-literacy level learners, in the adult literacy centres in Imenti-North Sub-County. The post-literacy programme is a part of continuing education that provides opportunities for adults and out-of-school youths to retain, improve and apply basic educational skills for personal, community and national development. The objectives of this paper was to examine the adult learners' performance in English language by analysing the errors they make in their written work and the causes of these errors. The theory used in this study is the Error Analysis theory by S.P. Corder (1974) and expanded by Ellis and Barkhuizen (2005) which was used to analyse the adult learners' errors in their written work. Methodology: The study utilised the Descriptive Research Design. Research was carried out in Imenti-North Sub-County, Kenya. The target population comprised 340 adult learners in the nine adult centres. A sample size of 60 adult learners from the Post Literacy Programme level was purposively chosen. The post literacy programme level learners were purposively chosen because English is used as a medium of instruction at this level and also studied as a subject. Data was collected by the use of an essay writing test for adult learners. Findings: The study established that there was poor performance in English language skills by adult learners as portrayed by the errors in their written work. Unique Contribution to Theory and Practice: The study recommends that adult English instructors should give learning tasks that are practical, comprehensible and must be relevant to important issues in the adult lives. The study further recommends that the government allocates more funds to the Directorate of Adult Education for the purchase of instructional resources in the learning centres, promote literacy surveys and curriculum development that meet the needs of adult and continuing adult learners.